Throwing speed in team handball: a systematic review - Vila, H.; Ferragut, C. (International Journal of Performance Analysis in Sport, 2019)
Its undeniable that throwing speed is one of the most important actions during handball match so it is really important for trainers to improve their knowledge about it. Thus, the aim of the article is threefold: a) to review the scientific studies about the factors that determine throwing speed in team handball to be able to establish the importance of each one b) to summarize the scientific knowledge about throwing speed in handball including aspects that need more studies c) To suggest practical recommendations for handball coaches. Our review revealed that; a) Players with greater elbow angles and higher elbow displacement angles at the release of the ball throw faster b) Hand size, biacromial breadth and finger length are the main anthropometric factors related to throwing speed c) handball players are able to reach a high throwing speeds without losing accuracy, so they should carry out their throwing speed training sessions always at high-speed d) There many different training proposals but with most of them throwing speed is improved. It is necessary to analyse the tactical-technical and conditional work related with throwing speed. e) There are very few studies made in real competition.